THE COMPARISON BETWEEN THE LANGUAGE USE BY MALE AND FEMALE IN SOCIAL MEDIA ON X - Putri, Jumriani Nadia; Sunra, La; Fitriyani, Fitriyani (State University of Makassar, 2026)
This study explores gender differences in language use on Social Media X, focusing on how male and female users employ language in their interactions. Using Domination Theory by Robin Lakoff (1970) as a framework, the research analyzes the language patterns of male and female users, highlighting distinct differences in communication styles. Female users are found to be more expressive, using language that emphasizes emotion, empathy, and relational bonding, while male users tend to prioritize rationality, factual communication, and problem-solving. The study reveals that females often use more words, show higher levels of emotional expression, and employ emoticons more frequently, whereas males use more direct, argumentative language and engage in competitive discourse. Additionally, males tend to use regional languages, while females favor standard Indonesian. The study also identifies key factors influencing language use, including gender-specific socialization, psychological traits, cultural expectations, and technological features of Social Media X. The findings suggest that while gender differences in language use are evident, both genders share common communication goals, such as message clarity and understanding. The research concludes that recognizing these gendered communication styles can improve social media interactions, enhance empathy, and reduce miscommunication, fostering more inclusive and effective online discourse. The study recommends training users on gender differences, promoting empathetic and rational communication, and supporting linguistic diversity on the platform to improve communication effectiveness. Keywords: Gender Differences, Language Use, Social Media X